Against the flow: evidence of multiple recent invasions of warmer continental shelf waters by a Southern Ocean brittle star - Sands, Chester J.; O'Hara, Timothy; Barnes, David K.; Martín-Ledo, Rafael (Frontiers in Ecology and Evolution, 2015)
The Southern Ocean is anomalously rich in benthos. This biodiversity is native, mostly endemic and perceived to be uniquely threatened from climate- and anthropogenically- mediated invasions. Major international scientific effort throughout the last decade has revealed more connectivity than expected between fauna north and south of the worlds strongest marine barrier – the Polar Front (the strongest jet of the Antarctic Circumpolar Current). To date though, no research has demonstrated any radiations of marine taxa out from the Southern Ocean, except at abyssal depths (where conditions differ much less). Our phylogeographic investigation of one of the most ubiquitous and abundant clades at high southern latitudes, the ophiuroids (brittlestars), shows that one of them, Ophiura lymani, has gone against the flow. Remarkably our genetic data suggest that O. lymani has successfully invaded the South American shelf from Antarctica at least three times, in recent (Pleistocene) radiation. Many previous studies have demonstrated links within clades across the PF this is the first in which northwards directional movement of a shelf-restricted species is the only convincing explanation. Rapid, recent, regional warming is likely to facilitate multiple range shift invasions into the Southern Ocean, whereas movement of cold adapted fauna (considered highly stenothermal) out of the Antarctic to warmer shelves has, until now, seemed highly unlikely.